Does Osteoarticular Allograft Reconstruction Achieve Long-term Survivorship after En Bloc Resection of Grade 3 Giant Cell Tumor of Bone?. Issue 11 (November 2020) - Albergo, Jose I.; Farfalli, German L.; Cabas-Geat, Angeles; Roitman, Pablo; Ayerza, Miguel A.; Aponte-Tinao, Luis A.
Abstract: Background: En bloc resection of benign tumors is only indicated in aggressive lesions with substantial destruction of the affected bone. Few reports have evaluated the long-term outcome of Grade 3 giant cell tumor of bone (GCTB; defined as severe bone destruction and soft tissue extension) treated with en bloc resection and reconstruction with a massive allograft. We recently reported that patients with benign tumors achieved better allograft reconstruction survivorship compared with those treated for a malignant bone tumor. In light of that finding, we wondered whether osteoarticular allografts would be a viable long-term alternative for Grade 3 GCTB, which could be important in some countries because of greater availability and lower costs compared with endoprostheses. Questions/purposes: We analyzed a group of patients with Grade 3 GCTBs treated with en bloc resection and osteoarticular allograft reconstruction in terms of (1) survivorship free from allograft removal at 10 years; (2) survivorship free from reoperation for any reason at 10 years, (3) functional results as measured by the Musculoskeletal Tumor Society (MSTS) score, (4) assessment of arthrosis at the knee. Methods: We retrospectively analyzed all patients with a Grade 3 GCTB treated between 1980 and 2007. Only patients treated with en bloc resection and reconstruction with massive osteoarticular allografts were included in the analysis. The indication for osteoarticular reconstruction during that time included severe bone destruction with intraarticular compromise of the tumor, intraarticular fracture because of tumor growth, the presence of inadequate remaining subchondral bone to resist normal loading (for the distal femur or proximal tibia), and the preservation of a soft-tissue component (ligaments or meniscus) for articular stability. During the period, 75 patients were treated with en bloc resection. Patients treated with intralesional curettage (n = 7), reconstruction with an endoprosthesis (n = 2), intercalary arthrodesis (n = 13), or unicondylar reconstruction (n = 14) were excluded. Of the original 75 treated with en bloc resection, 52% (39) were treated with osteoarticular allograft reconstruction, and no patient was lost to follow-up before 2 years or had substantial missing data. However, of the 39 patients, another 21% (8) have not been seen in the last 5 years, but these were included here because they reached the 10-year minimum surveillance period before being lost. Twenty-three of those 39 patients were previously reported by our group and 16 new patients (treated between 1980-1985) were included in this series (eight distal radius, six distal femur, two proximal tibias), extending the follow-up period and including more patients for analysis. The median (range) follow-up duration was 26 years (10 to 34). We assessed survivorship using a Kaplan-Meier analysis, we drew MSTS scores retrospectively from patients´ medical records, and we graded arthrosis using the Ahlbäck scale for the knee (which was by far the most common joint involved, n = 31, and so it was the joint we assessed for the presence of arthrosis). Results: The survivorship free from allograft removal was 85% at 10 years (95% CI 74 to 96). The allograft survivorship free from reoperation for any reason at 10 years was 72% (95% CI 59 to 87). The median (range) MSTS score was 28 points (19 to 30). The grade of arthrosis in the knee at last follow-up was analyzed in 20 patients and classified in nine as Ahlbäck Type 4, in six as Type 3, in three as Type 2 and in two as Type 5. Conclusions: Osteoarticular allograft reconstruction after a Grade 3 GCTB en bloc resection showed excellent long-term survivorship. We believe these results compare favorably with other studies on endoprosthetic reconstruction and head-to-head studies of these approaches should be performed; these would need to be multicenter trials. In the meantime, in locations where endoprostheses are unavailable or too expensive, we believe our results support the use of osteoarticular allografts. Level of Evidence: Level IV, therapeutic study.